2021
DOI: 10.21203/rs.3.rs-608655/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When hot meets cold: post-flare coronal rain

Abstract: All solar flares demonstrate a prolonged, hourlong post-flare (or gradual) phase, characterized by arcade-like, post-flare loops (PFLs) visible in many extreme ultraviolet (EUV) passbands. These coronal loops are filled with hot – ~30MK – and dense plasma, evaporated from the chromosphere during the impulsive phase of the flare, and they very gradually recover to normal coronal density and temperature conditions. During this gradual cooling down to ~1MK regimes, much cooler – ~0.01MK – and denser coronal rain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The initial density and temperature profiles are obtained from a 2.5D atmosphere relaxation simulation with a uniform upward magnetic field, in which the C7 temperature profile from Avrett & Loeser (2008), a density profile calculated based on hydrostatic equilibrium, and an adaptive background heating are employed. More details on the relaxation are available in Ruan et al (2021) and the results are demonstrated in Fig. 1.…”
Section: Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial density and temperature profiles are obtained from a 2.5D atmosphere relaxation simulation with a uniform upward magnetic field, in which the C7 temperature profile from Avrett & Loeser (2008), a density profile calculated based on hydrostatic equilibrium, and an adaptive background heating are employed. More details on the relaxation are available in Ruan et al (2021) and the results are demonstrated in Fig. 1.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…The study of solar flares led to the standard flare scenario based on lightcurve variations and detailed spatio-temporally resolved images. This standard flare model has been modeled frequently in 2D magnetohydrodynamic settings where a vertical current sheet is evolved to a flare loop configuration, and is recently revisited with a number of advanced 3D simulations (Shen et al 2022;Ruan et al 2023;Wang et al 2023), as well as with 2.5D models where self-consistent two-way coupling between electron beams and the multidimensional MHD scenario is incorporated (Ruan et al 2020;Druett et al 2023b), or where post-flare coronal rain is obtained in multi-D settings (Ruan et al 2021). It should be noted that these models deliberately adopt a simple initial magnetic topology, and as yet do not involve the actual full flux rope eruption process, but rather concentrate on the realistic thermodynamic and energetic evolution in and below the current sheet region.…”
Section: Introductionmentioning
confidence: 99%
“…Coronal rain is a widely observed phenomenon where dense and cool condensations form in the hot corona, and then fall down along magnetic loops to the solar surface . It was first reported around 50 years ago (Kawaguchi 1970;Leroy 1972), and appears frequently in non-flaring coronal loops (Schrijver 2001;Antolin 2020) and post-flare loops (Scullion et al 2016;Ruan et al 2021). Coronal rain has been observed off-limb and on-disk in chromospheric lines (e.g., Ca II H and Hα) and transition region (TR) lines (e.g., Si IV), as well as in extreme ultraviolet (EUV) observations (Schrijver 2001;Verwichte et al 2017;Li et al 2020;Ishikawa et al 2020).…”
Section: Introductionmentioning
confidence: 97%